Pattern of Lung findings in HRCT Scan of Vaccinated and Non-vaccinated RT-PCR Positive COVID-19 Patients (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Coronavirus disease 2019 (COVID- 19) is a highly infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV- 2). Large-scale vaccination of risk groups and later the general population is the single most effective public health measure for mitigation of the COVID-19 pandemic. Methods and Materials: This prospective cross sectional study was carried out at DNCC dedicated covid-19 hospital, Mohakhali, Dhaka, enrolling 50 (fifty) non vaccinated and fifty (50) vaccinated RT-PCR positive Covid-19 patients. Results: Majority of the patients were >50 years old in both groups. Most of the patients had bilateral lung involvement and ground glass, fibrotic change was the predominant CT pattern in both groups. 64% of non vaccinated patients had consolidation which is significantly higher than the vaccinated group (20%). Non vaccinated patients had more severe disease than vaccinated patients, 84% and 18% respectively. Percentage of lung involvement was significantly higher in non vaccinated group. Vaccinated patients had to stay less number of days (mean 6.2 days) in hospital than non-vaccinated patients (15.24 days). Death rate of non vaccinated (20%) Covid-19 patient was significantly higher than vaccinated (2%) patients. Conclusion: Vaccination can effectively reduce mortality and morbidity of Covid-19 patients by reducing the active number of cases as well as severity of the disease.BJRI, 2024; VOL. 32(2): 130-138